Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Effectiveness of Key Biodiversity Areas in representing global avian diversity - Tom P. Lansley; Olivia Crowe; Stuart H. M. Butchart; David P. Edwards; Gavin H. Thomas (Conservation Biology, 2025)
Key Biodiversity Areas (KBAs) are the largest and most complete network of significant sites for the global persistence of biodiversity. Although important sites for birds worldwide have been relatively well assessed, a key question is how effectively the global KBA network represents avian diversity. We identified bird species, orders, habitats, and geographic regions that are underrepresented by KBAs. Area of Habitat (AOH) maps for 10,517 terrestrial bird species were cropped and masked by the extent of each KBA. Almost all species had at least one part of their seasonal distribution in one or more KBAs. Twenty‐nine species had no habitat overlap with KBAs, and 1900 species had 2 ). Terrestrial bird species of tropical forests were 12.8% better represented in KBAs than expected by chance, whereas boreal and temperate forest species were less well represented than expected by chance (74.4% and 25.1%, respectively). Among avian orders, Anseriformes and Charadriiformes were underrepresented in KBAs (29.0% and 17.9%, respectively), whereas Trogoniformes and Psittaciformes were better represented (16.2% and 6.9%, respectively) than expected by chance. Bird species for potential KBA identification include marsh antwren ( Formicivora paludicola ) and Tabar pitta ( Erythropitta splendida ). These are mainly due to recent changes in species’ taxonomy or their International Union for Conservation of Nature Red List category. Identifying poorly represented species and where they occur highlights shortfalls where expansion of the network could bring conservation benefits.

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Unveiling growth and carbon composition of macroalgae with different strategies under global change - Camino F. de la Hoz; Paul R. Brooks; Jennifer Coughlan; Inés Mazarrasa; Elvira Ramos; Samuel Sainz-Villegas; Araceli Puente; Jose A. Juanes; Tasman P. Crowe (Marine Environmental Research, 2025)

Valuing plurality: Environmental humanities approaches to ecosystem services and Nature's Contributions to People - Tomas Buitendijk; Ashley Cahillane; John Brannigan; Tasman P. Crowe (Environmental Science & Policy, 2024)

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

The influence of environmental context on community composition in artificial rockpools associated with seawalls - Veronica Farrugia Drakard; Ally J. Evans; Tasman P. Crowe; Pippa J. Moore; Jennifer Coughlan; Paul R. Brooks (Marine Environmental Research, 2024)

A response-surface approach into the interactive effects of multiple stressors reveals new insights into complex responses - Paul R. Brooks; Mark Anthony Browne; Lisandro Benedetti-Cecchi; Devin A. Lyons; Tasman P. Crowe (Frontiers in Marine Science, 2023)
Understanding the difficult to predict interactive effects of anthropogenic stressors is recognized as one of the major challenges facing environmental scientists and ecosystem managers. Despite burgeoning research, predicting stressor interactions is still difficult, in part because the same two stressors can interact, or not, depending on their intensities. While laboratory experiments have provided useful insights about how organisms respond to serial doses of single stressors, we lack ‘response-surface’ field experiments in which naturally occurring assemblages are exposed to multiple types and concentrations of stressors. Here we used a field-based dosing system combined with a ‘response-surface’ design to test the individual and combined effects of two stressors (copper and chlorpyrifos) at five concentrations of each, for a total of 25 replicated treatments (n=4). After six weeks of dosing, chemical uptake and impacts at several levels of biological organization in mussel assemblages were measured. Stressor combinations produced interactive effects that would not have been revealed without using this replicated ‘response-surface approach’. Results show that non-additive effects of multiple stressors may be more complex and more common than previously thought. Additionally, our findings suggest that interactive effects of multiple stressors vary across levels of organization which has implications for monitoring and managing the chemical, biological and ecological impacts of priority pollutants in the real world.

Population structure and reproductive states of the dogwhelk Nucella lapillus differ between artificial structures and natural rocky shores - Bryan Thompson; Paul R. Brooks; Veronica Farrugia Drakard; Fiona Kubin; Hannah S. Earp; Ignacio Alvarez-Cienfuegos; Pippa J. Moore; Tasman P. Crowe (Marine Environmental Research, 2023)

Using valve gape analysis to compare sensitivity of native Mytilus edulis to invasive Magallana gigas when exposed to heavy metal contamination - David B. Kelleghan; Luke O'Callaghan; Freddie Huggard; Tasman P. Crowe; Paul R. Brooks (Marine Environmental Research, 2023)

Artificial rockpools: Seaweed colonisation and productivity vary between sites but are consistent across environmental contexts - Veronica Farrugia Drakard; Ally J. Evans; Tasman P. Crowe; Pippa J. Moore; Jennifer Coughlan; Paul R. Brooks (Marine Environmental Research, 2023)

Colonisation after disturbance on artificial structures: The influence of timing and grazing - Veronica Farrugia Drakard; Paul R. Brooks; Tasman P. Crowe (Marine Environmental Research, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

Assessing discards in an illegal small-scale fishery using fisher-led reporting - T. Mendo; J. Mendo; J. M. Ransijn; I. Gomez; P. Gil-Kodaka; J. Fernández; R. Delgado; A. Travezaño; R. Arroyo; K. Loza; P. McCann; S. Crowe; et al. (Reviews in Fish Biology and Fisheries, 2022)
About a third of all marine fish in the world are caught in Small-Scale Fisheries (SSF). SSF are increasingly recognised as essential for food security and livelihoods for vulnerable and economically fragile communities globally. Although individual SSF vessels are usually perceived as having little impact on the ecosystem, the cumulative impact of gear type and number of vessels may be substantial. Bottom trawling is a common fishing method that can greatly influence the marine ecosystem by damaging the seafloor and generating high levels of discards. However, appropriate sampling coverage using on-board observer programmes to collect these data from SSF are rare, as they are expensive and pose logistical constraints. A mobile App was used to assess whether self-reporting by fishers could provide reliable fine-scale information on fishing effort and discards over time in an illegal shrimp trawling fishery in northern Peru. Maps depicting the spatial distribution of trawling effort and the proportion of discards from observers and fishers were compared using the Similarity in Means (SIM) Index, which ranges from 0 when spatial patterns differ completely to 1 when spatial patterns are very similar. High levels of agreement between spatio-temporal patterns of effort (SIM Index = 0.81) and discards (0.96) were found between fisher and observer maps. Moreover, far greater spatial coverage was accomplished by fishers, suggesting that self-reporting via an App represents a useful approach to collect reliable fisheries data as an initial step for effective monitoring and management of these fisheries.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The use of environmental DNA metabarcoding and quantitative PCR for molecular detection of marine invasive non-native species associated with artificial structures - Laura M. Gargan; Paul R. Brooks; Siobhan R. Vye; Joseph E. Ironside; Stuart R. Jenkins; Tasman P. Crowe; Jens Carlsson (Biological Invasions, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Quasi-simultaneous 3D printing of muscle-, lung- and bone-equivalent media: a proof-of-concept study - T. Kairn; M. Zahrani; N. Cassim; A. G. Livingstone; P. H. Charles; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2020)

Assessing the fit of 3D printed bolus from CT, optical scanner and photogrammetry methods - S. K. Maxwell; P. H. Charles; N. Cassim; T. Kairn; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2020)

Sampling and Processing Methods Impact Microbial Community Structure and Potential Activity in a Seasonally Anoxic Fjord: Saanich Inlet, British Columbia - Mónica Torres-Beltrán; Andreas Mueller; Melanie Scofield; Maria G. Pachiadaki; Craig Taylor; Kateryna Tyshchenko; Céline Michiels; Phyllis Lam; Osvaldo Ulloa; Klaus Jürgens; Jung-Ho Hyun; Virginia P. Edgcomb; et al. (Frontiers in Marine Science, 2019)

Characterization of large basking shark Cetorhinus maximus aggregations in the western North Atlantic Ocean - L. M. Crowe; O. O'Brien; T. H. Curtis; S. M. Leiter; R. D. Kenney; P. Duley; S. D. Kraus (Journal of Fish Biology, 2018)
Cetorhinus maximus aggregations recorded during extensive aerial survey efforts off the north‐eastern United States between 1980 and 2013 included aggregations centring on sightings with group sizes of at least 30 individuals. These aggregations occurred in summer and autumn months and included aggregation sizes of up to 1398 individuals, the largest aggregation ever reported for this species. The aggregations were associated with sea surface temperatures of 13–24° C and chlorophyll‐a concentrations of 0·4–2·6 mg m −3 and during one aggregation, a high abundance of zooplankton prey was present. Photogrammetric tools allowed for the estimation of total body lengths ranging between 4 and 8 m. Characterization of these events provides new insight into the potential biological function of large aggregations in this species.

Diverse effects of invasive ecosystem engineers on marine biodiversity and ecosystem functions: A global review and meta‐analysis - Tamar Guy‐Haim; Devin A. Lyons; Jonne Kotta; Henn Ojaveer; Ana M. Queirós; Eva Chatzinikolaou; Christos Arvanitidis; Serena Como; Paolo Magni; Andrew J. Blight; Helen Orav‐Kotta; Paul J. Somerfield; et al. (Global Change Biology, 2018)
Invasive ecosystem engineers ( IEE ) are potentially one of the most influential types of biological invaders. They are expected to have extensive ecological impacts by altering the physical–chemical structure of ecosystems, thereby changing the rules of existence for a broad range of resident biota. To test the generality of this expectation, we used a global systematic review and meta‐analysis to examine IEE effects on the abundance of individual species and communities, biodiversity (using several indices) and ecosystem functions, focusing on marine and estuarine environments. We found that IEE had a significant effect (positive and negative) in most studies testing impacts on individual species, but the overall (cumulative) effect size was small and negative. Many individual studies showed strong IEE effects on community abundance and diversity, but the direction of effects was variable, leading to statistically non‐significant overall effects in most categories. In contrast, there was a strong overall effect on most ecosystem functions we examined. IEE negatively affected metabolic functions and primary production, but positively affected nutrient flux, sedimentation and decomposition. We use the results to develop a conceptual model by highlighting pathways whereby IEE impact communities and ecosystem functions, and identify several sources of research bias in the IEE ‐related invasion literature. Only a few of the studies simultaneously quantified IEE effects on community/diversity and ecosystem functions. Therefore, understanding how IEE may alter biodiversity–ecosystem function relationships should be a primary focus of future studies of invasion biology. Moreover, the clear effects of IEE on ecosystem functions detected in our study suggest that scientists and environmental managers ought to examine how the effects of IEE might be manifested in the services that marine ecosystems provide to humans.

Ecological impacts of non-native Pacific oysters (Crassostrea gigas) and management measures for protected areas in Europe - Roger J. H. Herbert; John Humphreys; Clare. J. Davies; Caroline Roberts; Steve Fletcher; Tasman. P. Crowe (Biodiversity and Conservation, 2016)

There are no whole truths in meta‐analyses: all their truths are half‐truths - Devin A. Lyons; Christos Arvanitidis; Andrew J. Blight; Eva Chatzinikolaou; Tamar Guy‐Haim; Jonne Kotta; Ana M. Queirós; Gil Rilov; Paul J. Somerfield; Tasman P. Crowe (Global Change Biology, 2016)

Heterotrophic bacteria from an extremely phosphate‐poor lake have conditionally reduced phosphorus demand and utilize diverse sources of phosphorus - Mengyin Yao; Felix J. Elling; CarriAyne Jones; Sulung Nomosatryo; Christopher P. Long; Sean A. Crowe; Maciek R. Antoniewicz; Kai‐Uwe Hinrichs; Julia A. Maresca (Environmental Microbiology, 2016)
Summary Heterotrophic P roteobacteria and A ctinobacteria were isolated from L ake M atano, I ndonesia, a stratified, ferruginous (iron‐rich), ultra‐oligotrophic lake with phosphate concentrations below 50 nM. Here, we describe the growth of eight strains of heterotrophic bacteria on a variety of soluble and insoluble sources of phosphorus. When transferred to medium without added phosphorus ( P ), the isolates grow slowly, their RNA content falls to as low as 1% of cellular dry weight, and 86–100% of the membrane lipids are replaced with amino‐ or glycolipids. Similar changes in lipid composition have been observed in marine photoautotrophs and soil heterotrophs, and similar flexibility in phosphorus sources has been demonstrated in marine and soil‐dwelling heterotrophs. Our results demonstrate that heterotrophs isolated from this unusual environment alter their macromolecular composition, which allows the organisms to grow efficiently even in their extremely phosphorus‐limited environment.

Macroalgal blooms alter community structure and primary productivity in marine ecosystems - Devin A. Lyons; Christos Arvanitidis; Andrew J. Blight; Eva Chatzinikolaou; Tamar Guy‐Haim; Jonne Kotta; Helen Orav‐Kotta; Ana M. Queirós; Gil Rilov; Paul J. Somerfield; Tasman P. Crowe (Global Change Biology, 2014)
Eutrophication, coupled with loss of herbivory due to habitat degradation and overharvesting, has increased the frequency and severity of macroalgal blooms worldwide. Macroalgal blooms interfere with human activities in coastal areas, and sometimes necessitate costly algal removal programmes. They also have many detrimental effects on marine and estuarine ecosystems, including induction of hypoxia, release of toxic hydrogen sulphide into the sediments and atmosphere, and the loss of ecologically and economically important species. However, macroalgal blooms can also increase habitat complexity, provide organisms with food and shelter, and reduce other problems associated with eutrophication. These contrasting effects make their overall ecological impacts unclear. We conducted a systematic review and meta‐analysis to estimate the overall effects of macroalgal blooms on several key measures of ecosystem structure and functioning in marine ecosystems. We also evaluated some of the ecological and methodological factors that might explain the highly variable effects observed in different studies. Averaged across all studies, macroalgal blooms had negative effects on the abundance and species richness of marine organisms, but blooms by different algal taxa had different consequences, ranging from strong negative to strong positive effects. Blooms' effects on species richness also depended on the habitat where they occurred, with the strongest negative effects seen in sandy or muddy subtidal habitats and in the rocky intertidal. Invertebrate communities also appeared to be particularly sensitive to blooms, suffering reductions in their abundance, species richness, and diversity. The total net primary productivity, gross primary productivity, and respiration of benthic ecosystems were higher during macroalgal blooms, but blooms had negative effects on the productivity and respiration of other organisms. These results suggest that, in addition to their direct social and economic costs, macroalgal blooms have ecological effects that may alter their capacity to deliver important ecosystem services.

Climate‐driven spatial mismatches between British orchards and their pollinators: increased risks of pollination deficits - Chiara Polce; Michael P Garratt; Mette Termansen; Julian Ramirez‐Villegas; Andrew J Challinor; Martin G Lappage; Nigel D Boatman; Andrew Crowe; Ayenew Melese Endalew; Simon G Potts; Kate E Somerwill; Jacobus C Biesmeijer (Global Change Biology, 2014)
Understanding how climate change can affect crop‐pollinator systems helps predict potential geographical mismatches between a crop and its pollinators, and therefore identify areas vulnerable to loss of pollination services. We examined the distribution of orchard species (apples, pears, plums and other top fruits) and their pollinators in Great Britain, for present and future climatic conditions projected for 2050 under the SRES A1B Emissions Scenario. We used a relative index of pollinator availability as a proxy for pollination service. At present, there is a large spatial overlap between orchards and their pollinators, but predictions for 2050 revealed that the most suitable areas for orchards corresponded to low pollinator availability. However, we found that pollinator availability may persist in areas currently used for fruit production, which are predicted to provide suboptimal environmental suitability for orchard species in the future. Our results may be used to identify mitigation options to safeguard orchard production against the risk of pollination failure in Great Britain over the next 50 years; for instance, choosing fruit tree varieties that are adapted to future climatic conditions, or boosting wild pollinators through improving landscape resources. Our approach can be readily applied to other regions and crop systems, and expanded to include different climatic scenarios.

Context- and density-dependent effects of introduced oysters on biodiversity - Dannielle S. Green; Tasman P. Crowe (Biological Invasions, 2014)

Impacts of the invasive alga Sargassum muticum on ecosystem functioning and food web structure - Tânia Salvaterra; Dannielle S. Green; Tasman P. Crowe; Eoin J. O’Gorman (Biological Invasions, 2013)

Environmental factors associated with invasion: modelling occurrence data from a coordinated sampling programme for Pacific oysters - Judith Kochmann; Francis O’Beirn; Jon Yearsley; Tasman P. Crowe (Biological Invasions, 2013)

Effects of Non-indigenous Oysters on Ecosystem Processes Vary with Abundance and Context - Dannielle S. Green; Carlos Rocha; Tasman P. Crowe (Ecosystems, 2013)

Multiple anthropogenic stressors and the structural properties of food webs - Eoin J. O'Gorman; Jayne E. Fitch; Tasman P. Crowe (Ecology, 2012)
Coastal environments are among the most productive on the planet, providing a wide range of ecosystem services. Development and exploitation mean that they are faced with stresses from a number of anthropogenic sources. Such stresses are typically studied in isolation, but multiple stressors can combine in unexpected ways to alter the structure of ecological systems. Here, we experimentally explore the impacts of inorganic nutrients and organic matter on a range of food web properties. We find that these two stressors combine additively to produce significant increases in connectance and mean food chain length. Such increases are typically associated with enhanced robustness to secondary extinctions and productivity, respectively. Despite these apparent beneficial effects, we find a simplification of web structure in terms of taxon richness and diversity, and altered proportions of basal and top species. These effects are driven by a reduction in community assembly and lower consistency in a range of system properties as a result of the multiple stressors. Consequently, impacted food webs are likely to be more vulnerable to human‐ or climate‐induced perturbations in the long term.

Impacts of invasion by Dreissena polymorpha (Pallas, 1771) on the performance of macroinvertebrate assessment tools for eutrophication pressure in lakes - Javier Atalah; Mary Kelly-Quinn; Kenneth Irvine; Tasman P. Crowe (Hydrobiologia, 2010)

A magnetoencephalography study of choice bias - William M. Hedgcock; David A. Crowe; Arthur C. Leuthold; Apostolos P. Georgopoulos (Experimental Brain Research, 2010)

Competition and habitat suitability: small-scale segregation underpins large-scale coexistence of key species on temperate rocky shores - Louise Bridget Firth; Tasman P. Crowe (Oecologia, 2010)

Disturbance of intertidal soft sediment assemblages caused by swinging boat moorings - R. J. H. Herbert; T. P. Crowe; S. Bray; M. Sheader (Hydrobiologia, 2009)

Predicting impacts of climate‐induced range expansion: an experimental framework and a test involving key grazers on temperate rocky shores - LOUISE B. FIRTH; TASMAN P. CROWE; PIPPA MOORE; RICHARD C. THOMPSON; STEPHEN J. HAWKINS (Global Change Biology, 2009)
Climate change has strong potential to modify the structure and functioning of ecosystems, but experimental field studies into its effects are rare. On rocky shores, grazing limpets strongly affect ecosystem structure and their distribution in NW Europe is changing in response to climate change. Three limpet species co‐occur in SW Britain ( Patella vulgata, Patella ulyssiponensis and Patella depressa ) on open rock and in pools. Shores in Ireland are similar, but currently lack P. depressa . It is anticipated that P. depressa will expand its range into Ireland as the climate warms, but we currently lack an empirical basis to predict the consequences of this change. Recent studies show that increasing abundance of P. depressa on British shores has been accompanied by a decline of P. vulgata suggesting interspecific competition. In this study, a new experimental framework was used to examine the potential for P. depressa to affect P. vulgata on Irish shores. P. vulgata was experimentally transplanted into enclosures on open rock and in pools in both Ireland and Britain. In pools, treatments also included transplanted P. ulyssiponensis to mimic natural assemblages. Growth and mortality of P. vulgata were measured over 6 months with no differences between Ireland and Britain. In Britain, P. vulgata caged in pools with transplanted P. depressa and P. ulyssiponensis showed reduced growth, compared with when caged in pools with P. ulyssiponensis alone. There was no effect of P. depressa on the growth rate of P. vulgata on open rock. Results indicate that if the range of P. depressa extends into Ireland, it would reduce the growth of P. vulgata where it co‐occurs with P. ulyssiponensis in pools. The framework used here provides a field‐based approach that could be used to examine the impacts of climate‐induced range expansions on the structure and functioning of other ecosystems.

Vessel Diameter Measurement from Intravital Microscopy - Jaesung Lee; Artit C. Jirapatnakul; Anthony P. Reeves; William E. Crowe; Ingrid H. Sarelius (Annals of Biomedical Engineering, 2009)

Large-scale coexistence and small-scale segregation of key species on rocky shores - Louise B. Firth; Tasman P. Crowe (Hydrobiologia, 2008)

Green manure effects on soil quality in relation to suppression of Verticillium wilt of potatoes - N. Ochiai; M. L. Powelson; F. J. Crowe; R. P. Dick (Biology and Fertility of Soils, 2008)

Histamine induces interleukin-6 expression in the human synovial sarcoma cell line (SW982) through the H1 receptor - S. L. Wang; S. Malany; Q. Wang; M. A. Santos; P. D. Crowe; R. A. Maki (Inflammation Research, 2006)

Pollination Ecology and Seed Production of Rhododendron Ponticum in Native and Exotic Habitats - Jane C. Stout; John A. N. Parnell; Juan Arroyo; Tasman P. Crowe (Biodiversity and Conservation, 2006)

Mental maze solving: directional fMRI tuning and population coding in the superior parietal lobule - Pavlos Gourtzelidis; Charidimos Tzagarakis; Scott M. Lewis; David A. Crowe; Edward Auerbach; Trenton A. Jerde; Kâmil Uğurbil; Apostolos P. Georgopoulos (Experimental Brain Research, 2005)

Neural activity in prefrontal cortex during copying geometrical shapes - Bruno B. Averbeck; David A. Crowe; Matthew V. Chafee; Apostolos P. Georgopoulos (Experimental Brain Research, 2003)

Neural activity in prefrontal cortex during copying geometrical shapes - Bruno B. Averbeck; Matthew V. Chafee; David A. Crowe; Apostolos P. Georgopoulos (Experimental Brain Research, 2003)

Workshop on Indices and Indicators for Climate Extremes, Asheville, NC, USA, 3–6 June 1997 Breakout Group C: Temperature Indices for Climate Extremes - C.K. Folland; C. Miller; D. Bader; M. Crowe; P. Jones; N. Plummer; M. Richman; D.E. Parker; J. Rogers; P. Scholefield (Climatic Change, 1999)

Multidimensional scaling analyses of two construction-related tasks - Kenneth C. Whang; David A. Crowe; A. P. Georgopoulos (Experimental Brain Research, 1999)

Bacteraemia in the Adult Intensive Care Unit of a Teaching Hospital in Nottingham, UK, 1985-1996 - M. Crowe; P. Ispahani; H. Humphreys; T. Kelley; R. Winter (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Bacteraemia in the adult intensive care unit of a teaching hospital in Nottingham, UK, 1985–1996 - M. Crowe; P. Ispahani; H. Humphreys; T. Kelley; R. Winter (European Journal of Clinical Microbiology & Infectious Diseases, 1998)